4+11z-1=9z+35-2z

Simple and best practice solution for 4+11z-1=9z+35-2z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+11z-1=9z+35-2z equation:


Simplifying
4 + 11z + -1 = 9z + 35 + -2z

Reorder the terms:
4 + -1 + 11z = 9z + 35 + -2z

Combine like terms: 4 + -1 = 3
3 + 11z = 9z + 35 + -2z

Reorder the terms:
3 + 11z = 35 + 9z + -2z

Combine like terms: 9z + -2z = 7z
3 + 11z = 35 + 7z

Solving
3 + 11z = 35 + 7z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-7z' to each side of the equation.
3 + 11z + -7z = 35 + 7z + -7z

Combine like terms: 11z + -7z = 4z
3 + 4z = 35 + 7z + -7z

Combine like terms: 7z + -7z = 0
3 + 4z = 35 + 0
3 + 4z = 35

Add '-3' to each side of the equation.
3 + -3 + 4z = 35 + -3

Combine like terms: 3 + -3 = 0
0 + 4z = 35 + -3
4z = 35 + -3

Combine like terms: 35 + -3 = 32
4z = 32

Divide each side by '4'.
z = 8

Simplifying
z = 8

See similar equations:

| 5r-7=2r+2 | | x^2+21-54=0 | | 3w^2-11w-20=0 | | 4x-(2x-5)=11 | | 4x-(2x-5)=11 | | 4x-(2x-5)=11 | | 4.67=r-.34 | | .22=log(x) | | 21-3(2w+1)=6w-3(6+w) | | -9=p-2 | | 4w^2-25w-21=0 | | 2(2-3n)=-[5n-(4-n)] | | b+.67=2 | | 15x-5=6x-68 | | 3x+2-6x=11+2x-15 | | 3-8x=-5-6x | | .1y-30=16-0.06y | | 42-4x=-11x | | 6x-(3x-2)+(4x-5)=2x+(4x-5) | | b-(-3b-3)=4b+3 | | 2+(5+y)= | | 2=3(4)-1 | | 72-10x=20x | | 8h^2k-32k=0 | | 14x+2+10x+50=8x | | 12x^2-30-[3(x^2-1)+4]= | | 6x+9=-7+5x | | d=168-144 | | x^2+9x+18=I | | d=168-24 | | d=168-12t | | (-3x^6)(5x^9)= |

Equations solver categories